Methodology for researching corporate disclosure of business social responsibility: Information base and stages of implementation - O. V. Efimova; O. V. Rozhnova (Учёт. Анализ. Аудит)
This article continues a series of publications on the issues of accounting, analysis and assessment of the corporate social responsibility in a rapidly changing environment when society and business face new challenges. The authors provide methodological solutions to the problem of studying the social responsibility of Russian public companies based on the analysis of data disclosed in their financial and non-financial statements. The research uses abduction methods; logical analysis; logical content analysis of financial and non-financial reporting standards in terms of requirements for disclosure of social aspects; expert analysis of social reporting of Russian companies; linguistic analysis in order to identify the practice of using certain terms and concepts in the financial and non-financial reporting. The analysis of corporate reporting standards made it possible to propose a new model for analyzing disclosures in the field of corporate social responsibility. The authors reveal the most important issues of the corporate social responsibility by assessing the trends in the social sphere, identifying opportunities and threats for its further development connected with the evolution of society, economy and ecology, ongoing digitalization processes. Procedures of researching business social responsibility are developed and fully described. The documentary base of the research includes International Financial Reporting Standards, Sustainable Development Reporting Standards, Basic Performance Indicators of the Russian Union of Industrialists and Entrepreneurs (RSPP) as well as financial and non-financial reports of Russian companies operating in production industries. The results of the research are the proposals to apply the multi-stage approach, which makes it possible to assess the social responsibility of certain economic entities through the prism of global tasks the country and the world community face with. The analysis of the complex problems of business and civilization allows us to identify five top problems in the light of which the social responsibility of large companies should be assessed, as well as to build a logical connection between these top problems and the key topics of disclosures in corporate reports.